2014
DOI: 10.1007/s11295-014-0778-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three QTL detection models on biochemical, sensory, and yield characters in Coffea canephora

Abstract: Coffea canephora is subject to enormous competitive challenges from other crops, especially for farmer sustainability and consumer requirements. Coffee breeding programs have to focus on specific traits linked to these two key targets, such as quality character, largely depending on the bean's biochemical composition and field yield. Two segregating populations A and B, from crosses between a hybrid (Congolese×Guinean) FRT58 parental clone and a Congolese FRT51 genotype and between two Congolese parents FRT67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The high‐density Robusta genetic map generated from this study will not only be useful in ordering future genetic maps such as the one for Arabica, but also in providing a higher marker density than the previous one (Mérot‐L'Anthoëne et al ., ). It will aid in selecting appropriate markers for various molecular breeding applications and in tracking introgression within each linkage group.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The high‐density Robusta genetic map generated from this study will not only be useful in ordering future genetic maps such as the one for Arabica, but also in providing a higher marker density than the previous one (Mérot‐L'Anthoëne et al ., ). It will aid in selecting appropriate markers for various molecular breeding applications and in tracking introgression within each linkage group.…”
Section: Discussionmentioning
confidence: 97%
“…The mapping of 1307 (15.2%) of the Coffee8.5K SNPs on the C. canephora map (BP409 X Q121) demonstrates the usefulness of the Coffee8.5K for developing high‐density genetic maps for this species. Combined with previously developed markers (Denoeud et al ., ; Mérot‐L'Anthoëne et al ., ), we obtained a reliable and accurate final map of 3039 markers, including 665 SNPs in coding regions, with only a low fraction of distorted markers. The total map length was 1370 cM with an average distance of 2.2 cM between markers.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The good performance of the GS method highlights the importance of this tool in the Coffea genus. To the best of our knowledge, molecular studies have been reported in coffee; however, most of them are still based on traditional molecular approaches (Ferrão et al 2013;Cubry et al 2013;Mérot-L'Anthoëne et al 2014). Large-scale genotyping expands their utility.…”
Section: Discussionmentioning
confidence: 99%